Studi Pelaksanaan Strategi Pembelajaran Inkuiri Pada Pembelajaran Geografi di SMA Negeri 2 Tondano - Keterina Refualu; Selvana Treni Tewal; Hermon Maurits Karwur (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2022)
This study aims to describe the effectiveness of the application of inquiry learning strategies in meeting the achievement of student competencies, namely learning outcomes. The research method uses descriptive and quantitative analysis. The research was conducted in class XI IPS SMA Negeri 2 Tondano. Data collection techniques include observation, interviews, tests, and documentation. Data analysis techniques in the form of tabulations, percentages, and conclusions. The results of the study show that the learning process using the inquiry learning model, observing activities by students in an environment close to their own lives, can effectively improve learning outcomes. The standard for measuring learning success is if the learning group has 80% of students with a mastery achievement score of 70. There are 26 students, or 92.8%, who get an achievement score of 70, and there are 2 students, or 7.1%, who are classified as having a learning achievement score of 70.